Separation membrane
The integration of tabular particles with a specific aspect ratio on the surface of the separation functional layer addresses the issue of membrane defects and enhances separation performance under various conditions.
Patent Information
- Application Number
- JP2024151123
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-08
- Filing Date
- 2024-09-03
- Publication Date
- 2025-03-21
AI Technical Summary
Existing separation membranes are prone to defects and breaks due to vibrations and shocks during transportation or installation, leading to reduced separation performance.
A separation membrane with a separation functional layer featuring tabular particles having an aspect ratio of 3 to 100 on its surface, which enhances durability and stability.
The membrane effectively suppresses defects and maintains excellent separation performance even under conditions of vibration and shock.
Smart Images

Figure 2025039536000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a separation membrane. [Background technology]
[0002] Membrane separation is a method for selectively separating and purifying specific components from various mixed gases and liquids. Membrane separation is driven by the pressure difference and concentration difference that occur between the supply side and the permeate side of a separation membrane, and is therefore attracting attention as a more energy-efficient method than other fluid separation methods.
[0003] For example, in natural gas refining plants, the main component methane gas and the impurity carbon dioxide are separated and refined, but by utilizing membrane separation, the high ejection pressure of the raw natural gas, over several MPa, can be utilized for separation and refinement.
[0004] In the membrane separation method, the separation membrane is used as a separation membrane module fixed to a housing, but if the membrane is defective or broken due to vibration or impact during transportation or installation, or due to expansion and contraction of the membrane during actual use, the separation performance will be significantly reduced due to leakage from the defect or break. As a method for improving the durability of the membrane, a method of coating the surface with particles having a particle size smaller than that of the membrane itself (see Patent Document 1) has been disclosed. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2018-158304 A Summary of the Invention [Problem to be solved by the invention]
[0006] Patent Document 1 discloses a zeolite membrane element having a structure of a porous support-zeolite membrane composite in which a zeolite membrane is formed on the surface of a porous support, the zeolite membrane being composed of coarse particles having a first average particle size (D1) and fine particles having a second average particle size (D2) smaller than the first average particle size (D1), the fine particles being precipitated on the surface of a zeolite membrane body composed of the coarse particles, and the particle size ratio (Dr), defined as the size (D1 / D2) of the first average particle size (D1) based on the second average particle size (D2), satisfies the condition of 2≦Dr≦10. However, the method of Patent Document 1 improves durability by covering the grain boundaries of coarse particles with fine particles, which have low durability, to suppress exposure of the grain boundaries, but has a problem that, when the membranes come into contact with each other or when an external stress is applied to the membrane, the fine particles get caught on each other on the membrane surface or stress is concentrated on the fine particles, which easily generates defects on the membrane surface. In addition, the contact area between the membrane surface and the fine particles is small, and there is concern that the particles may fall off during transportation or use.
[0007] Therefore, an object of the present invention is to provide a separation membrane that can stably exhibit separation performance even after transportation and during use. [Means for solving the problem]
[0008] In order to solve the above problems, the present invention has the following configuration.
[0009] A separation membrane having a separation functional layer, the separation functional layer comprising tabular particles having an aspect ratio of 3 or more and 100 or less present on a surface of the separation functional layer. Effect of the Invention
[0010] Even if the separation membrane of the present invention is subjected to vibration or impact during transportation or installation, or the membrane expands and contracts during actual use, the tabular particles present on the surface of the separation functional layer move, thereby suppressing the occurrence of defects and breakage, and allowing the membrane to exhibit excellent separation performance. [Brief description of the drawings]
[0011] [Figure 1] 1 shows a schematic cross-sectional view of a separation membrane. [Diagram 2] 1 shows a schematic cross-sectional view of a separation membrane in which tabular particles are present on the surface of a curved separating functional layer. [Diagram 3] A schematic diagram illustrating the definition of the aspect ratio of a tabular grain is shown. [Figure 4] A schematic diagram illustrating the definition of the aspect ratio of a tabular grain is shown. [Diagram 5] A schematic diagram illustrating the definition of the aspect ratio of a tabular grain is shown. [Figure 6] 1 shows a schematic cross-sectional view of a separation membrane in which tabular particles are laminated on the surface of a separation functional layer. [Figure 7] 1 shows a schematic cross-sectional view of a separation membrane in which tabular particles are laminated on the surface of a separation functional layer. [Figure 8] FIG. 2 shows a schematic cross-sectional view of a separation membrane module housing a separation membrane. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will now be described by way of example with reference to the drawings, but the present invention should not be construed as being limited to the examples shown in the drawings.
[0013] The present invention is a separation membrane having a separation functional layer, in which tabular grains having an aspect ratio of 3 or more and 100 or less are present on the surface of the separation functional layer.
[0014] The separation membrane of the present invention has a separation functional layer, that is, a layer that functions as a separation layer for the substance to be separated.
[0015] The separation membrane of the present invention may be a free-standing membrane having only a separation functional layer, or a composite membrane in which a separation functional layer is combined with the outer surface of a support. The separation membrane of the present invention is preferably a composite membrane because it has improved pressure resistance and strength.
[0016] A cross-sectional schematic diagram of the separation membrane of the present invention when it is a composite membrane is shown in Figure 1. The separation membrane 4 of the present invention comprises a support 2, a separation functional layer 3, and tabular particles 1 present on the surface of the separation functional layer.
[0017] The separation membrane of the present invention is not particularly limited, but a carbon membrane is preferably used as a free-standing membrane, and a carbon membrane, a zeolite membrane, or a metal-organic framework (MOF) membrane is preferably used as a separation functional layer of a composite membrane, with a carbon membrane being more preferably used as the separation functional layer from the viewpoints of durability and low cost.
[0018] The carbon component ratio of the carbon membrane is preferably 60% by weight or more and 98% by weight or less. A carbon component ratio of 60% by weight or more improves the heat resistance and chemical resistance of the separation membrane. The carbon component ratio of the carbon membrane is more preferably 65% by weight or more, and even more preferably 70% by weight or more. Furthermore, a carbon component ratio of the carbon membrane of 98% by weight or less improves flexibility and handleability, and increases interaction with surface functional groups, making it easier to coat, particularly when used as a tabular particle dispersion, so that the carbon membrane is more preferably 90% by weight or less, and even more preferably 85% by weight or less.
[0019] The carbon component ratio of a carbon membrane is the weight fraction of the carbon component when the total of the organic element components measured by X-ray photoelectron spectroscopy (XPS) is taken as 100%. If the separation membrane is a composite membrane, it refers to the carbon component ratio of the separation functional layer portion, but if the boundary between the separation functional layer and the support portion is unclear, it may be the carbon component ratio of the entire separation membrane including the support.
[0020] Examples of carbon membranes suitable as the separation functional layer of the free-standing membrane and the composite membrane include membranes obtained by carbonizing polyphenylene oxide, polyvinyl alcohol, polyacrylonitrile, phenol resin, wholly aromatic polyester, unsaturated polyester resin, alkyd resin, melamine resin, urea resin, polyimide resin, diallyl phthalate resin, lignin resin, urethane resin, etc. Two or more of these may be used.
[0021] Zeolite membranes suitable for use as the separation functional layer of the composite membrane include membranes made of aluminosilicates, such as NaX type (FAU), ZSM-5, MOR, silicalite, and A type. Two or more of these may be used. Zeolite species preferably have a Si / Al ratio similar to that of the species grown secondarily by hydrothermal synthesis reaction.
[0022] Examples of MOF membranes suitable for use as the separation functional layer of the composite membrane include membranes made of Cu-BTC, MOF-5, IRMOF-3, MIL-47, MIL-53, MIL-96, MMOF, SIM-1, ZIF-7, ZIF-8, ZIF-22, ZIF-69, ZIF-90, etc. Two or more of these may be used.
[0023] As the support of the composite membrane, for example, porous inorganic materials such as alumina, silica, cordierite, zirconia, titania, vycor glass, zeolite, magnesia, sintered metal, and porous carbon materials obtained by carbonizing porous organic materials made of carbonizable resins are preferably used. Examples of carbonizable resins include polyphenylene oxide, polyvinyl alcohol, polyacrylonitrile, phenolic resins, wholly aromatic polyesters, unsaturated polyester resins, alkyd resins, melamine resins, urea resins, polyimide resins, diallyl phthalate resins, lignin resins, and urethane resins. Two or more of these may be used. From the viewpoint of durability and low cost, a porous carbon material mainly composed of carbon is more preferably used as the support.
[0024] In order to improve the permeability of the permeable components contained in the substances to be separated, nanoparticles can be added to the separation functional layer. Examples of nanoparticles include silica, titania, zeolite, metal oxides, MOFs, and carbon nanotubes (CNTs).
[0025] In the separation membrane of the present invention, even if the membrane area is increased, the surface of the separation membrane is protected by the plate-like particles, so that even if the membrane area is increased when packed in a case, defects and breakage are unlikely to occur during transportation or use, and from the viewpoint of improving the membrane area relative to the packing rate, the shape of the separation membrane is preferably fibrous. Here, fibrous refers to a membrane having a ratio of length to the average diameter of the separation membrane (length / average diameter of the separation membrane) of 100 or more.
[0026] For a fibrous separation membrane, the shape of the fiber cross section is not particularly limited, and any shape such as a hollow cross section, a circular cross section, a polygonal cross section, a multi-leaf cross section, or a flat cross section can be used. However, a hollow cross section, i.e., a hollow fiber-shaped separation membrane, is preferred because it reduces pressure loss within the membrane and improves the permeability of the separation membrane.
[0027] In the separation membrane of the present invention, tabular grains are present on the surface of the separation functional layer. When the separation membrane is a composite membrane, the surface of the separation functional layer refers to the surface on the opposite side to the support.
[0028] The state in which the tabular particles are present on the surface of the separation functional layer can be confirmed by observing a cross section perpendicular to the fiber axis of the separation membrane after embedding in the resin using a scanning electron microscope or a transmission electron microscope.
[0029] An embodiment in which tabular particles are present on the surface of the separation functional layer will be described with reference to FIG.
[0030] 2 is a schematic cross-sectional view of the separation membrane of the present invention including a curved separation functional layer, which shows an embodiment in which a curved separation functional layer 3 and one or more tabular particles 1 are present, with the tabular particles being present on the surface of the separation functional layer.
[0031] The tabular grains of the present invention have an aspect ratio of 3 to 100. The aspect ratio herein refers to the ratio Ll / T of the longest side Ll to the thickness T of each tabular grain. The longest side Ll is the diameter of the smallest circumscribing circle for the surface S1 having the largest area observed two-dimensionally by rotating a three-dimensional image obtained using a method capable of grasping the structure three-dimensionally, such as three-dimensional microscopy. The thickness T is the length of the largest perpendicular line passing through the point where the sides constituting the surface S2 intersect among the perpendicular lines to Ll with respect to the largest surface S2 observed two-dimensionally obtained by rotating the three-dimensional image of the tabular grain 90 degrees around the longest side Ll as the rotation axis.
[0032] The three-dimensional microscope photography is not particularly limited as long as it is possible to observe a single particle, but it is preferable to appropriately select an analysis method that can separate, observe, and analyze individual particles as electronic information, such as slice & view, which cuts out a cross section with an ion beam and continuously observes it with a scanning electron microscope, or a method of applying computer tomography using a transmission X-ray or electron microscope. If it is difficult to observe a single tabular particle on the surface of the separation functional layer, it is preferable to use a method that can appropriately observe a single particle, such as dispersing the tabular particle peeled off from the separation functional layer in a liquid such as water, dripping the dispersion onto a plate, drying it, and observing it.
[0033] The definition of the longest side Ll will be described with reference to FIG.
[0034] 3 shows the form of a tabular grain in which the number of faces observed as a three-dimensional image differs from the number of faces observed as a two-dimensional image. The diameter of the minimum circumscribing circle of the maximum face S1;5 obtained two-dimensionally by rotating the three-dimensional image is defined as L1;6.
[0035] A method for calculating the thickness T will be described with reference to FIG. 4 and FIG.
[0036] Figure 4 shows the form of a tabular grain whose maximum face is the face that constitutes the tabular grain, and the three-dimensional image of the tabular grain is rotated 90 degrees around L1 as the rotation axis to obtain the maximum face S2;7 observed two-dimensionally. The length of the maximum perpendicular line of Ll that passes through the point where the sides that constitute face S2 intersect is taken as the thickness T;8.
[0037] FIG. 5 shows the form of a tabular grain in which the maximum face is not a face constituting a tabular grain (such as an oblong spheroid), and the three-dimensional image of the tabular grain is rotated 90 degrees around L1 as the rotation axis to obtain the maximum face S2;7 observed two-dimensionally. The length of the maximum perpendicular line passing through two points on face S2 among the perpendicular lines to Ll is defined as the thickness T;8.
[0038] The longest side Ll and thickness T of a tabular grain are measured for any 10 tabular grains using a method capable of grasping the structure three-dimensionally, such as 3D microscopy, and the measurements are calculated as the average of the 10 measurements.
[0039] The aspect ratio is calculated by repeating the above-calculated ratio of the longest side Ll to the thickness T (Ll / T) 10 times arbitrarily while changing the field of view, and calculating the average value of the 10 times.
[0040] As described above, the aspect ratio of the tabular grains of the present invention is 3 or more and 100 or less, but more preferably 5 or more and 95 or less. When the aspect ratio of the tabular grains is 3 or more, the tabular grains are easily stacked, and when the separation membranes contact each other or the separation membrane contacts the housing, the tabular grains act as a buffer, and the protective effect is high, which is preferable. The aspect ratio is 5 or more, more preferably 10 or more, and even more preferably 20 or more. When the aspect ratio is 100 or less, it is preferable that the area where the tabular grains overlap each other can be increased, and when the tabular grains dispersed in the liquid are stacked, they can be uniformly dispersed while maintaining the fluidity of the liquid. The aspect ratio is 95 or less, more preferably 90 or less, and even more preferably 80 or less.
[0041] The tabular particles are preferably inorganic particles from the viewpoints of chemical resistance, heat resistance, etc. For example, graphene, graphene oxide, silica, talc, mica, silver, etc. are more preferably used, and talc, mica, and silver are even more preferably used because they have high lubricity and are easy to move, and have a high buffer effect when contacting the separation membrane.
[0042] The tabular particles present on the surface of the separation functional layer of the separation membrane of the present invention preferably have a Vickers hardness of 40 or more and 100 or less. The Vickers hardness of the tabular particles is preferably 40 or more, since it is easier to form the tabular particles on the surface of the separation functional layer. The Vickers hardness is more preferably 45 or more, and even more preferably 50 or more. The Vickers hardness of the tabular particles is preferably 100 or less, since it enhances the effect of protecting the separation functional layer when the separation membranes come into contact with each other. The Vickers hardness is more preferably 90 or less, and even more preferably 80 or less.
[0043] It is preferable that at least a part of the tabular particles present on the surface of the separation functional layer of the separation membrane of the present invention is laminated on the surface of the separation functional layer. The term "tabular particles are laminated on the surface of the separation functional layer" refers to a state in which an arbitrary point on the surface of the separation functional layer has a normal line intersecting with two or more tabular particles. The state in which the tabular particles are laminated on the surface of the separation functional layer can be observed in a field of view in which 50 or more particles are present on the surface of the separation functional layer by using a method capable of observing the cross section as a two-dimensional image, such as a method of observing the cross section perpendicular to the fiber axis of the resin-embedded separation membrane with a scanning electron microscope or a method of irradiating with an ion beam and observing with a transmission electron microscope. When there are not 50 or more particles in one data, data obtained from another observation field is added to calculate so that the total number of particles is 50 or more.
[0044] The laminated tabular grains will be explained with reference to FIGS.
[0045] The stacked tabular grains in the separation membrane of the present invention may be in either one of the following modes: one tabular grain is in contact with the surface of the separation functional layer and the other stacked tabular grains are not in contact with the surface of the separation functional layer as shown in Figure 6, or two tabular grains are in contact with the surface of the separation functional layer and the tabular grains overlap each other as shown in Figure 7. In either mode, at any point on the surface of the separation functional layer, there is a normal 9 that intersects with two or more tabular grains on the side where the point exists.
[0046] In the separation membrane of the present invention, the ratio of the laminated tabular particles on the surface of the separation functional layer is preferably 50% or more and 110% or less. If the laminated ratio is 50% or more, even when the separation membrane comes into contact and stress is applied from all directions, the tabular particles move to disperse the stress applied to the surface of the separation functional layer, which is preferable because it enhances the protective effect. The laminated ratio is more preferably 55% or more, and even more preferably 60% or more. If the laminated ratio is 110% or less, it is preferable from the viewpoint of suppressing an increase in the permeation resistance against the permeating components of the substance to be separated. The laminated ratio is more preferably 100% or less, and even more preferably 90% or less.
[0047] The ratio of the flat particles stacked on the surface of the separation functional layer is expressed by the ratio of the number of particles in the first stage to the number of particles in the second stage (number of particles in the second stage / number of particles in the first stage), where the first flat particle from the side closest to the point is the first stage and the second flat particle is the second stage (number of particles in the second stage / number of particles in the first stage). The ratio of the flat particles stacked on the surface of the separation functional layer can be observed in a field where 50 or more particles in the first stage are present on the surface of the separation functional layer using a method that can observe the cross section as a two-dimensional image, such as a method of observing a cross section perpendicular to the fiber axis of a resin-embedded separation membrane with a scanning electron microscope or a method of irradiating an ion beam and observing with a transmission electron microscope. If there are not 50 or more particles in one data, data obtained from another observation field is added to calculate so that the number of particles in the first stage is 50 or more. The ratio of stacking is calculated by observing 10 arbitrary points on the surface of the separation functional layer and averaging the ratios of the 10 particles obtained. A state in which the proportion of stacked tabular grains is 100% or more indicates an embodiment in which the particle size of the second stage grains is smaller than that of the first stage grains, and the number of second stage grains is greater than the number of first stage grains.
[0048] In the separation membrane of the present invention, the surface coverage of the separation functional layer of the tabular particles is preferably 20% or more and 90% or less. A surface coverage of 20% or more is preferable because it increases the probability that tabular particles are present at the contact surface between the separation membranes or between the separation membrane and the housing, thereby enhancing the protective effect. A surface coverage of 30% or more is more preferable, and 50% or more is even more preferable. A surface coverage of 90% or less is preferable from the viewpoint of suppressing an increase in the permeation resistance against the permeating components of the substance to be separated. A surface coverage of 80% or less is more preferable, and 70% or less is even more preferable.
[0049] The surface coverage of the separation functional layer by tabular particles can be calculated by a method that can separate the particles and the separation functional layer as electronic information of a two-dimensional image, for example, by observing the surface of the separation functional layer on which the tabular particles are stacked with a scanning electron microscope or a transmission electron microscope, and combining elemental analysis as necessary. The surface of the separation functional layer can be calculated as the percentage of tabular particles present in 100% of the separation functional layer in a field of view in which 50 or more particles are present in the data. If there are not 50 or more particles in one data, data obtained from another observation field is added to calculate so that the total number of particles is 50 or more. The surface coverage is calculated by observing 10 arbitrary points on the surface of the separation functional layer and averaging the coverage of the 10 obtained.
[0050] The separation membrane of the present invention preferably satisfies the following formula 1. 10 ≦ D / Ll ≦ 5000...Formula 1 [In formula 1, D represents the average diameter of the separation membrane (nm), and Ll represents the longest side of the tabular particle (nm)] D / Ll is preferably 10 or more, since it reduces the possibility of peeling or detachment of tabular grains. D / Ll is more preferably 20 or more, and even more preferably 50 or more. On the other hand, D / Ll of 5000 or less is preferable, since it makes the tabular grains denser and more likely to form a layered state. D / Ll is more preferably 2000 or less, and even more preferably 1000 or less.
[0051] The separation membrane average diameter D is the diameter of the separation functional layer in a cross section perpendicular to the fiber axis when the separation membrane is a fibrous free-standing membrane, and the combined diameter of the separation functional layer and support in a cross section perpendicular to the fiber axis when the separation membrane is a fibrous composite membrane. The separation membrane average diameter D can be calculated as the average of the longest length Dl and the shortest length Ds of the cross section or layered surface using a method that allows observation as a two-dimensional image, such as a scanning electron microscope or a transmission electron microscope. The separation membrane average diameter D is calculated as the average of 10 points taken at any one separation membrane cross section or layered surface.
[0052] The thickness of the tabular particle layer, i.e., the layer in which the tabular particles are laminated, is not particularly limited, but is preferably 10 nm or more and 10 μm or less. The thickness of the tabular particle layer is preferably 10 nm or more, since it is easier to obtain a buffer effect when the separation membrane comes into contact with the tabular particle layer. The thickness of the tabular particle layer is more preferably 20 nm or more, and even more preferably 50 nm or more. In addition, the thickness of the tabular particle layer is preferably 10 μm or less, since it is possible to improve the permeation flux of the substance to be separated. The thickness of the tabular particle layer is more preferably 5 μm or less, and even more preferably 1 μm or less.
[0053] The thickness of the flat particle layer is determined by drawing a normal to the separation functional layer at any point on the surface of the separation functional layer using a method that can observe a cross section perpendicular to the fiber axis of the resin-embedded separation membrane as a two-dimensional image, such as a scanning electron microscope or a transmission electron microscope, and taking the intersection point between the normal to the separation functional layer and the outermost surface of the flat particle layer, and the distance between these points (normal distance) is taken as the thickness. The thickness is measured at 20 points on the surface of the separation functional layer and calculated as the average value of the 20 points.
[0054] The porosity of the flat particle layer is preferably 10% or more and 70% or less. When the porosity of the flat particle layer is 10% or more, the flat particle layer does not increase the permeation resistance, and the permeability decrease can be suppressed. The porosity of the flat particle layer is more preferably 20% or more, and even more preferably 30% or more. On the other hand, when the porosity of the flat particle layer is 70% or less, defects and breakage can be easily suppressed even when the membranes contact each other. The porosity of the flat particle layer is more preferably 65% or less, and even more preferably 60% or less.
[0055] The porosity of the tabular grain layer is a value calculated by the following formula, where the region of the tabular grain layer is set from an image observed by three-dimensional microscopy, the volume of the region of the tabular grain layer is A, and the volume of the voids in the tabular grain layer is B. When the tabular grains are not stacked, i.e., there is only one layer, the porosity in the present invention refers to the porosity of the one-layer portion.
[0056] Porosity (%)=B / A×100 The porosity can be observed in a visual field where there are 50 or more tabular grains. If there are not 50 or more tabular grains in one data point, data from another visual field is added so that the number of tabular grains becomes 50 or more. The porosity is calculated by observing 10 arbitrary points in the tabular grain layer and averaging the proportions of the 10 particles obtained.
[0057] The three-dimensional microscope photography is not particularly limited as long as it can separate and observe the solid and void parts that constitute the tabular particle layer, but it is preferable to appropriately select an analysis method that can separate, observe, and analyze the solid and void parts as electronic information, such as slice & view, in which a cross section is cut out with an ion beam and continuously observed with a scanning electron microscope, or a method of applying computer tomography using a transmission X-ray or electron microscope. If the electron beam contrast between the solid and void parts is weak and observation is difficult, it is preferable to perform electronic staining using a suitable metal or the like before observation.
[0058] The method for laminating tabular grains onto the separation functional layer is not particularly limited, and any method can be used, such as immersing the separation membrane in a dispersion liquid in which tabular grains are dispersed in a liquid, applying a dispersion liquid of tabular grains using a spray, or directly spraying tabular grains. From the viewpoint of forming a uniform tabular grain layer on the surface of the separation functional layer, the method of immersing the separation membrane in a dispersion liquid of tabular grains is preferred.
[0059] Examples of separation targets for the separation membrane of the present invention include carbon dioxide separation and storage systems from exhaust gases of power plants, blast furnaces, etc., removal of sulfur components from gasified fuel gas in integrated coal gasification combined cycle power generation, purification of biogas, purification of hydrogen from organic hydrides, purification of propylene in mixed gases in ethylene centers, etc. In other words, the separation membrane of the present invention is preferably a gas separation membrane.
[0060] From the viewpoint of increasing the gas treatment amount per unit volume, the separation membrane of the present invention is preferably used as a separation membrane module (hereinafter, may be simply referred to as "module") housed in a housing 10. Fig. 8 shows a schematic cross-sectional view of one embodiment of a separation membrane module housing the separation membrane of the present invention.
[0061] There are no particular limitations on the method of housing the separation membrane in the housing, so long as the structure does not allow the substances to be separated and the permeating components to mix, but examples include static potting, in which one end of the module is sealed and a potting material is injected from the other end and allowed to harden, and centrifugal potting, in which a potting material is injected and allowed to harden while the module is rotating. Centrifugal potting is preferred because both ends can be fixed at once when modularizing.
[0062] Examples of the potting material used when storing the separation membrane include thermoplastic resins and thermosetting resins, and may further contain other additives.
[0063] Examples of thermoplastic resins used as potting materials include polyethylene, polyethersulfone, polystyrene, polyphenylene sulfide, polyarylate, polyester, liquid crystal polyester, polyamide, polymethyl methacrylate, etc. Examples of thermosetting resins include epoxy resins, unsaturated polyester resins, urethane resins, urea resins, phenolic resins, melamine resins, silicone resins, etc. Two or more of these may be used. Among these, epoxy resins and urethane resins are preferred from the viewpoint of the balance of moldability, curing time, adhesion, hardness, etc.
[0064] Examples of additives suitable for use in the potting material include fillers, surfactants, silane coupling agents, and rubber components. Examples of fillers include silica, talc, zeolite, calcium hydroxide, and calcium carbonate, which have the effects of suppressing heat generation during curing, improving strength, and thickening. The surfactant and silane coupling agent have the effects of improving the handleability when mixing the potting material and improving the infiltration between carbon membranes for fluid separation when filling the potting material. The rubber component has the effect of improving the toughness of the cured and molded potting material. The rubber component may be contained in the form of rubber particles.
[0065] In the separation membrane of the present invention, the cross-sectional shape of the housing is preferably elliptical or circular, more preferably circular, from the viewpoint of improving the pressure resistance of the housing. Here, the cross section of the housing refers to a cross section of the housing perpendicular to the longitudinal direction of the separation membrane. Examples of the material of the housing include metal, resin, fiber reinforced plastic (FRP), etc., and can be appropriately selected depending on the environment of the installation location and the situation of use. In applications requiring pressure resistance and heat resistance, metals that combine strength and moldability are preferred, and stainless steel, aluminum, and alloys thereof are more preferred.
[0066] The inlet and outlet for the substance to be separated arranged in the housing have the function of directing the substance to be separated to the separation membrane. When the separation membrane is used in a dead-end filtration method, it is sufficient that the separation membrane has at least one inlet and outlet for the substance to be separated, and when the separation membrane is used in a cross-flow filtration method, it is preferable that the separation membrane has two or more inlets and outlets for the substance to be separated in total. The separation membrane may have multiple inlets and outlets for the substance to be separated as long as the mechanical strength of the housing is maintained. In this case, in order to improve the membrane utilization efficiency by the diffusion of the fluid, it is preferable to place a cloth such as a mesh or felt between the inlet and the separation membrane as long as it does not hinder the passage of the fluid.
[0067] The plant of the present invention is a plant including the module of the present invention. The plant of the present invention is a plant constructed and installed on the sea or on land, for example, a plant constructed on a ship or a plant whose scaffolding is fixed to an anchor on the seabed. The separation membrane of the present invention can be suitably used in an offshore plant that is subject to vibrations caused by tides and wind, since the tabular particles have a cushioning effect.
[0068] In addition to the separation membrane or module, the plant preferably includes a pretreatment facility, a refined component recovery facility, a by-product recovery facility, and the like. The pretreatment facility is a facility for removing impurities in advance from the substance to be separated before separation, or for adjusting the composition of the substance to be separated before separation. The refined component recovery facility is a facility for recovering refined components obtained by removing unnecessary components from the substance to be separated before separation, and for further refining the components as necessary or for supplying them to a pipeline or the like. The by-product recovery facility is a facility for recovering by-products removed from the substance to be separated before separation, and for example discharging them after rendering them harmless.
[0069] In the plant of the present invention, it is preferable that the separation membrane or module, the pretreatment equipment, the purified component recovery equipment, and the by-product recovery equipment are connected by piping or the like, so that the substance to be separated before separation is continuously separated into the purified components and by-products. EXAMPLES
[0070] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited thereto. Evaluations in each of the examples and comparative examples were carried out by the following methods.
[0071] (Calculation of the stacking ratio of tabular particles on the surface of the separation functional layer) Using an epoxy resin embedding kit manufactured by Polysciences, the cross section of a hollow fiber carbon membrane in which the surface of the separation functional layer was embedded in resin was processed with a focused ion beam and observed with a transmission electron microscope. The particle layer was observed in a field of view in which 50 or more particles exist on the surface of the separation functional layer, and among the flat particles in which the normal line at any point of the separation functional layer intersects on the side where the point exists, the first flat particle from the side closest to the point was taken as the first stage, and the second flat particle was taken as the second stage. The ratio of the number of particles in the first stage to the number of particles in the second stage (number of particles in the second stage / number of particles in the first stage) was calculated as the stacking ratio. If there were not 50 or more particles in one data, data obtained from another observation field was added, and the calculation was performed so that the total number of particles was 50 or more.
[0072] (Calculation of particle aspect ratio) A part of the tabular particles present on the surface of the separation functional layer was peeled off using a release paper, and the aqueous dispersion was treated with an ultrasonic homogenizer at 20 kHz for 30 seconds, dropped onto the plate, and dried to produce a plate with only tabular particles present on the surface. A single particle on the plate was observed in 3D using a slice & view scanning electron microscope. The diameter of the smallest circumscribed circle for the surface S1 with the largest area observed two-dimensionally on the screen by rotating the obtained 3D image was taken as the longest side L1. In addition, the length of the maximum perpendicular line passing through the point where the sides that make up the surface S2 intersect among the perpendicular lines to L1 was calculated as the thickness T for the largest surface S2 observed two-dimensionally by rotating the obtained 3D image 90 degrees around the longest side L1 as the rotation axis, and the aspect ratio was calculated as the ratio (L1 / T) of the two. The longest side Ll and thickness T of the tabular grains were measured for 10 randomly selected tabular grains and calculated as the average value of the 10 points. The aspect ratio was calculated by taking the ratio of the longest side Ll to the thickness T (Ll / T), which was repeated 10 times at random by changing the field of view, and the average value of the 10 measurements was calculated.
[0073] (Calculation of void ratio of tabular particle layer) From an image observed by Slice & View, the region of the tabular grain layer was set, and the volume of the region of the tabular grain layer was defined as A and the volume of the void portion of the tabular grain layer was defined as B, and the values were calculated by the following formula.
[0074] Porosity (%)=B / A×100 The porosity was determined by observing a visual field in which 50 or more tabular grains were present. When there were not 50 or more tabular grains in one data point, data from another visual field was added to calculate so that the number of tabular grains was 50 or more. Ten random points in the tabular grain layer were observed, and the porosity was calculated as the average value of the proportions of the 10 grains.
[0075] (Calculation of surface coverage of separation functional layer) The surface of the separation functional layer on which particles are layered was observed using a scanning electron microscope, and the percentage of tabular particles present in a field of view where 50 or more particles were present in the data was calculated relative to 100% of the separation functional layer. If there were not 50 or more particles in one data point, data from another observation field was added, and the calculation was made so that the total number of particles was 50 or more. The surface coverage was calculated by observing 10 random points on the surface of the separation functional layer, and averaging the coverage rates of the 10 particles obtained.
[0076] (Calculation of the average separation membrane diameter D) The porous carbon support-separation functional layer composite membrane was observed using a scanning electron microscope, and the average length Dl of the longest part of the cross section and the average length Ds of the shortest part of the cross section were calculated. The average diameter D of the separation membrane was calculated as the average of 10 points on the cross section of the separation membrane.
[0077] (Calculation of particle layer thickness) Using an epoxy resin embedding kit manufactured by Polysciences, the cross section of a hollow fiber carbon membrane with the surface of the separation functional layer embedded in resin was observed with a scanning electron microscope. A normal line to the separation functional layer was drawn at any point on the surface of the separation functional layer, and the intersection point of the line with the outermost surface of the particle layer was taken, and the distance between the points (normal distance) was taken as the particle layer thickness. The particle layer thickness was taken at 20 arbitrary points on the surface of the separation functional layer, and calculated as the average value of the 20 points.
[0078] (Vickers hardness calculation) A part of the tabular particles present on the surface of the separation functional layer was peeled off using a release paper, and the obtained tabular particles were subjected to a hardness test using a micro Vickers hardness tester with a test force of 20 mN in accordance with the Vickers hardness test of JIS Z 2244-1 (2024). The Vickers hardness was measured for 10 random particles, and the average value of the 10 points was calculated.
[0079] (Frequency of defects after scratch test) One end of a hollow fiber carbon membrane cut to a length of 30 cm was fixed to a SUS support and the other end was left open. A melamine sponge with "Tracey (registered trademark)" attached to the contact surface was used to rub against the carbon membrane twice so that the rubbing surface was perpendicular to the surface.
[0080] One end of the hollow fiber carbon membrane after rubbing was fixed to a SUS support and the other end was left open. The hollow fiber carbon membrane was immersed in ethanol while being pressurized from the open end with an internal pressure of 0.2 MPaG, and the locations where bubbles were generated were counted as defects. Twenty hollow fiber carbon membranes were evaluated, and the number of defects per meter was taken as the defect frequency.
[0081] (Desorption rate of tabular grains) Ten hollow fiber carbon membranes cut to 1 cm length were centrifuged at a centrifugal acceleration of 64,000 times the gravity to remove some of the particles. The plate-like particles on the separation functional layer were peeled off using release paper, and an aqueous dispersion treated with an ultrasonic homogenizer at 20 kHz for 30 seconds was dropped onto a plate and dried to produce a plate with only plate-like particles present on the surface. The number of particles on the plate was counted using a scanning electron microscope, and the value calculated using the following formula was used when the number before removal was a [pieces] and the number after removal was b [pieces]. Desorption rate (%) = (1-b / a) x 100 The observation was carried out at an arbitrary position of one hollow fiber carbon membrane, and the average value of 10 membranes was calculated.
[0082] (Production Example 1: Preparation of hollow fiber porous carbon support) A spinning dope was prepared by mixing 10 parts by weight of polyacrylonitrile (PAN) (weight average molecular weight 150,000) manufactured by Polysciences Corporation, 10 parts by weight of polyvinylpyrrolidone (PVP) (weight average molecular weight 40,000) manufactured by Sigma-Aldrich Corporation, and 80 parts by weight of dimethyl sulfoxide (DMSO) manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., and stirring at 100°C.
[0083] After the obtained spinning dope was cooled to 25°C, a concentric triple spinneret was used to simultaneously discharge an 80 wt% DMSO aqueous solution from the inner tube, the spinning dope from the middle tube, and a 90 wt% DMSO aqueous solution from the outer tube, and then the raw yarn was obtained by leading the raw yarn to a coagulation bath of pure water at 25°C and winding it up on a roller. The obtained raw yarn was washed with water and then dried at 25°C for 24 hours using a circulating dryer to produce a precursor of a hollow fiber-shaped porous carbon support.
[0084] The obtained precursor of the porous carbon support was passed through an electric furnace at 250°C and heated in an air atmosphere for 1 hour to perform an infusible treatment, thereby obtaining an infusible yarn. The infusible yarn was then carbonized at a carbonization temperature of 550°C to obtain a porous carbon support having an outer diameter of 298 μm and an inner diameter of 100 μm.
[0085] (Production Example 2: Preparation of porous carbon support-separation functional layer composite membrane) Aromatic polyimide (hereinafter, aromatic PI) "Matrimid (registered trademark)" 5218 was dissolved in N-methylpyrrolidone (NMP) to prepare a 10 wt% aromatic polyimide solution (hereinafter, aromatic PI solution). Here, "Matrimid (registered trademark)" 5218 is a condensation product of 3,3',4,4'-benzophenonetetracarboxylic dianhydride and 5(6)-amino-1-(4'-aminophenyl)-1,3,3'-trimethylindane.
[0086] The porous carbon support of Production Example 1 was immersed in the PI solution, then pulled up at a speed of 10 mm / min, immersed in water to remove the solvent, and dried in a circulating hot air dryer to obtain a coated yarn in which the surface of the porous carbon support was coated with aromatic PI. The coated yarn was then carbonized at 550°C in an inert atmosphere to produce the separation membrane of Production Example 2, which is a porous carbon support-separation functional layer composite membrane. In the following examples and comparative examples, the separation membrane of Production Example 2, which was confirmed to have a defect frequency of 0 / m before the abrasion test, was used. At this time, the average diameter D was 300 μm.
[0087] Example 1 The separation membrane of Production Example 2 was immersed for 1 minute in a dispersion in which talc (SG-2000) manufactured by Nippon Talc Co., Ltd. was dispersed in water to a concentration of 10% by weight, and then dried at 50° C. for 2 hours to produce the separation membrane of Example 1 in which talc, which is a tabular particle, was laminated on the surface of the separation functional layer. As a result of evaluation by the above-mentioned method, the separation membrane of Example 1 had a porosity of 46%, a lamination ratio in the tabular particles of 82%, Ll of 1020 nm, a thickness T of 50 nm, an aspect ratio Ll / T of 20.4, a surface coverage rate of 78%, D / Ll of 294, a particle layer thickness of 200 nm, a Vickers hardness of 52, a defect frequency after a scratch test of 0.32 pieces / m, and a detachment ratio of the tabular particles of 9%.
[0088] Example 2 A separation membrane of Example 2 was produced in which talc was laminated on the surface of the separation functional layer in the same manner as in Example 1, except that the talc concentration in the dispersion was 2% by weight. As a result of evaluation by the above-mentioned method, the separation membrane of Example 2 had a porosity of 24%, a lamination ratio of 65%, Ll of 1020 nm, a thickness T of 50 nm, an aspect ratio Ll / T of 20.4, a surface coverage rate of 17%, D / Ll of 294, a particle layer thickness of 60 nm, a Vickers hardness of 52, a defect frequency after a scratch test of 0.56 pieces / m, and a detachment ratio of 10%.
[0089] Example 3 A separation membrane of Example 3 was produced in which talc was laminated on the surface of the separation functional layer in the same manner as in Example 1, except that a dispersion liquid in which talc was dispersed in water to a concentration of 2% by weight was used and separated by centrifugation at 42,000 rpm. As a result of evaluation by the above-mentioned method, the separation membrane of Example 3 had a porosity of 10%, a lamination ratio of 34%, Ll of 320 nm, a thickness T of 50 nm, an aspect ratio Ll / T of 6.4, a surface coverage rate of 64%, D / Ll of 938, a particle layer thickness of 880 nm, a Vickers hardness of 42, a defect frequency after a scratch test of 1.3 pieces / m, and a detachment ratio of 9%.
[0090] Example 4 A separation membrane of Example 4 was produced by laminating graphene oxide on the surface of the separation functional layer in the same manner as in Example 1, except that a nanographene oxide dispersion solution (G-20-1) manufactured by EM Japan was used instead of the dispersion solution in which talc was dispersed. As a result of evaluation by the above-mentioned method, the separation membrane of Example 4 had a porosity of 12%, a lamination ratio of 38%, Ll of 90 nm, a thickness T of 1 nm, an aspect ratio Ll / T of 90, a surface coverage rate of 46%, D / Ll of 3333, a particle layer thickness of 64 nm, a Vickers hardness of 62, a defect frequency after a scratch test of 1.6 pieces / m, and a detachment ratio of 27%.
[0091] Example 5 A separation membrane of Example 6 was produced in the same manner as in Example 1, except that a dispersion liquid in which silver nanoparticles (M612) manufactured by Tokusen Kogyo Co., Ltd. were dispersed in water to a concentration of 2% by weight was used, in which silver nanoparticles were laminated on the surface of the separation functional layer. As a result of evaluation by the above-mentioned method, the separation membrane of Example 5 had a longest side Ll of 7840 nm, a porosity of 43%, a lamination ratio of 40%, an aspect ratio Ll / T of 98, a surface coverage rate of 52%, a D / Ll of 38, a Vickers hardness of 80, a defect frequency after a scratch test of 1.2 pieces / m, and a detachment ratio of 14%.
[0092] Comparative Example 1 A separation membrane of Comparative Example 1 was produced in the same manner as in Production Example 2. As a result of evaluation by the above-mentioned method, the separation membrane of Comparative Example 1 had a defect frequency of 3.1 defects / m after the scratch test.
[0093] Comparative Example 2 A separation membrane of Comparative Example 2 was produced in the same manner as in Example 1, except that a graphene layer was formed on the surface of the separation functional layer instead of the dispersion liquid in which talc was dispersed, using graphene nanopowder (G-12) manufactured by EM Japan Co., Ltd. As a result of evaluation by the above-mentioned method, the separation membrane of Comparative Example 2 had a porosity of 9%, a lamination ratio of 78%, Ll of 4500 nm, a thickness T of 12 nm, an aspect ratio Ll / T of 375, a surface coverage rate of 75%, D / Ll of 50, a particle layer thickness of 40 nm, a Vickers hardness of 63, a defect frequency after a scratch test of 1.4 pieces / m, and a detachment ratio of 41%.
[0094] Comparative Example 3 The separation membrane of Production Example 2 was immersed in a dispersion liquid in which zeolite powder was dispersed in water for 1 minute, and dried at 50 ° C for 12 hours to coat the surface of the separation functional layer with zeolite seed crystals. Next, an aqueous solution in which an alumina source, a silica source, sodium hydroxide, and tetraethylammonium hydroxide were dissolved in water was stirred at room temperature for 6 hours to prepare a synthetic liquid. The obtained synthetic liquid was filled into an autoclave, and the separation membrane of Production Example 2 coated with the seed crystals was immersed in the synthetic liquid and heated at 160 ° C for 6 hours to produce a separation membrane of Comparative Example 3 in which a zeolite layer was formed on the surface of the separation functional layer. As a result of evaluation by the above-mentioned method, the separation membrane of Comparative Example 3 had a porosity of 12%, a lamination ratio of 0%, Ll of 420 nm, a thickness T of 300 nm, an aspect ratio Ll / T of 1.4, a surface coverage ratio of 21%, D / Ll of 714, a particle layer thickness of 300 nm, a Vickers hardness of 172, a defect frequency after a scratch test of 1.6 pieces / m, and a detachment ratio of 76%.
[0095] Comparative Example 4 A separation membrane of Comparative Example 4 was produced in the same manner as in Example 1, except that instead of the dispersion liquid in which talc was dispersed, the silica particle dispersion liquid "Snowtex (registered trademark)" (MP-4540M) manufactured by Nissan Chemical Industries, Ltd. was immersed in a dispersion liquid diluted with water to a solid content concentration of 10% by weight. The separation membrane of Comparative Example 4 was produced in such a manner that a silica layer was formed on the surface of the separation functional layer. As a result of evaluation by the above-mentioned method, the separation membrane of Comparative Example 4 had a porosity of 12%, a lamination ratio of 15%, Ll of 450 nm, a thickness T of 410 nm, an aspect ratio Ll / T of 1.1, a surface coverage rate of 80%, D / Ll of 667, a particle layer thickness of 800 nm, a Vickers hardness of 1110, a defect frequency after a scratch test of 1.8 pieces / m, and a detachment ratio of 78%.
[0096] Comparative Example 5 A separation membrane of Comparative Example 5 was produced in the same manner as in Example 1, except that instead of the dispersion liquid in which talc was dispersed, the membrane was immersed in a dispersion liquid in which Yamaguchi Mica mica (TM-10) was diluted with water to a solid content concentration of 10% by weight. As a result of evaluation by the above-mentioned method, the separation membrane of Comparative Example 5 had a porosity of 10%, a lamination ratio of 73%, Ll of 11000 nm, a thickness T of 85 nm, an aspect ratio Ll / T of 129, a surface coverage rate of 82%, D / Ll of 27, a particle layer thickness of 200 nm, a Vickers hardness of 150, a defect frequency after a scratch test of 1.7 pieces / m, and a detachment ratio of 43%. Comparative Example 6 A separation membrane of Comparative Example 6 was produced by laminating graphene oxide on the surface of the separation functional layer in the same manner as in Example 1, except that a graphene oxide dispersion solution (G-20S) manufactured by EM Japan was used instead of the dispersion solution in which talc was dispersed. As a result of evaluation by the above-mentioned method, the separation membrane of Comparative Example 6 had a porosity of 15%, a lamination ratio of 44%, Ll of 4000 nm, a thickness T of 37 nm, an aspect ratio Ll / T of 110, a surface coverage rate of 55%, D / Ll of 75, a particle layer thickness of 90 nm, a Vickers hardness of 113, a defect frequency after a scratch test of 2.1 pieces / m, and a detachment ratio of 33%.
[0097] [Table 1] [Explanation of symbols]
[0098] 1: Tabular grains 2:Support 3: Separation functional layer 4: Separation membrane 5: Surface S1 6: Longest side Ll 7: Surface S2 8: Thickness T 9:Normal 10: Housing 11: Potting material 12: Inlet / outlet for the material to be separated
Claims
1. A separation membrane having a separation functional layer, the separation membrane comprising tabular grains having an aspect ratio of 3 or more and 100 or less present on a surface of the separation functional layer.
2. 2. The separation membrane according to claim 1, wherein at least a portion of the tabular grains is laminated on a surface of the separation functional layer.
3. The separation membrane according to claim 2 , wherein the tabular particle layer has a thickness of 10 nm or more and 10 μm or less.
4. The separation membrane according to claim 3 , wherein the porosity of the tabular particle layer is from 10% to 70%.
5. 2. The separation membrane according to claim 1, wherein the aspect ratio of the tabular grains is 5 or more and 95 or less.
6. The separation membrane of claim 1 , wherein the separation membrane is fibrous.
7. 2. The separation membrane according to claim 1, wherein the tabular grains cover 20% to 90% of the surface of the separation functional layer.
8. The separation membrane according to claim 6 , wherein the longest side of the tabular grain and the average diameter of the separation membrane satisfy the following formula 1: 10≦D / Ll≦5000...Formula 1 [In the formula, Ll represents the longest side of the tabular grain, and D represents the average diameter of the separation membrane.]
9. The separation membrane according to claim 1 , wherein the tabular particles are inorganic particles.
10. 2. The separation membrane according to claim 1, wherein the tabular particles have a Vickers hardness of 40 or more and 100 or less.
11. 2. The separation membrane according to claim 1, wherein the tabular particles are talc or mica.
12. The separation membrane according to claim 1 , wherein the separation functional layer is a carbon membrane.
13. The separation membrane according to claim 1 , further comprising a support mainly composed of carbon.
14. A separation membrane module comprising the separation membrane according to any one of claims 1 to 13 housed in a housing.
15. A plant comprising the separation membrane module according to claim 14.
Citation Information
Patent Citations
Zeolite membrane element and method for producing the same
JP2018158304A